The Perceptions of Pesantren Principals on Teachers’ Professional Development - Hasrianti, Hasrianti; Ridwan, Nurul Haeriyah; Mulyati, Ariadna; Rahman, Ahmad Ardillah (Jurnal Kreatif Online, 2020)
In the context of Islamic Pesantren, principals have significant roles in enhancing teachers’ professional development. This study developed a critical phenomenological research to investigate the perceptions of principals in Pesantren on the notion of teachers’ professional development. The aim was to examine the understanding of principals at Rahmatul Asri Pesantren on characteristics associated with professional teachers as well as to examine their experiences related to their efforts and obstacles in enhancing teachers’ professional development in their school. Qualitative research was utilized by the researcher to understand the voices of Pesantren principals. Interviews were conducted with four school leaders using semi-structured interview. In terms of the principals’ understanding on the notion of professional teachers, this research has identified three significant themes as the attributes of professional teachers. Professional teachers have been linked to the ability of teachers to teach based on their educational background, the ability of teachers to instill spiritual and moral values on their pedagogical practices, and the ability of teachers to use computers and internet to create interesting materials. Several efforts have been made by the principals to enhance teachers’ professional development such as giving motivation and rewards to teachers, encouraging teachers to participate in trainings and workshops, and providing teachers with adequate teaching facilities. However, several obstacles were faced by the principals in developing teachers’ professional development. Those obstacles include the teachers’ double job, the difference of teachers’ academic background, and the lack of teachers’ discipline and technological expertise. This study has implications on how school principals in Pesantren and government should consider the ways in strengthening the school practices in Pesantren such as maximising the training and workshops for teachers, giving rewards to teachers, and instilling the religious values on school policies and practices.